FinTech and Its Dynamics in the Digital Revolution of Nepal - Vaidya, Rashesh (Kanya Journal, 2025)
Financial technology, or fintech, has become essential in Nepal’s digital economy. Banks and financial institutions in Nepal have implemented digital payment systems, allowing customers to conduct transactions without using cash. This study on the analysis of Nepal’s payment system (Mid-July 2022 to Mid-July 2025) documents a rapid digital financial transformation. The ecosystem is defined by a decisive shift from traditional channels towards mobile-first, real-time platforms like wallets, QR payments, and the Faster Payment System. This is supported by an explosive growth of over 23-fold increase (2,300 percent) in PSP agents, embedding digital finance within communities. The findings confirm a structural move to a more accessible and efficient financial landscape. The report details critical implications for policymakers, financial institutions, and businesses to foster sustainable growth and inclusion in this new paradigm.